The native stem holoparasitic Cuscuta japonica suppresses the invasive plant Ambrosia trifida and related mechanisms in different light conditions in northeast China - Wang, Wei-Bin; Gao, Fan-Fan; Feng, Wei-Wei; Wu, Qi-Ye; Feng, Yu-Long (Frontiers in Plant Science, 2022)
Increasing evidence from low latitude ranges has demonstrated that native parasitic plants are promising biocontrol agents for some major invasive weeds. However, related mechanism and the effect of environments on the control effect of the parasite are still unclear. In addition, few related studies have been conducted in high latitude (> 40 o), where the exotic plant richness is the highest in the globe, but natural enemies are relatively scarce. During field surveys, a Cuscuta species was found on the cosmopolitan invasive weed Ambrosia trifida L. in Shenyang, northeast China. Here we first studied the impacts of the parasite on the invader at three sites with different light regimes and related mechanism, then the haustorial connections between the parasite and the invader using anatomy and measurement of carbon (C) and nitrogen (N) stable isotope compositions (δ13C, δ15N), and finally identified the parasite using two molecular marks. The parasite was identified as C. japonica Choisy. This native holoparasitic vine posed serious C rather than N limitation to the invader, explaining its greatly inhibitory effects on the invader. Its negative effects were stronger on reproductive relative to vegetative growth; and at high relative to low light habitats, which indicated that the higher the vigor of the host is, the higher the impact of the parasite pose. The parasite could establish haustorial connections with phloem, xylem and pith of the invader, and thus obtain resources from both leaves and roots, which was confirmed by difference of δ13C and δ15N between the two species. The parasite had significantly higher leaf C concentration and δ13C than its invasive host, being a strong C sink of the parasitic association. Our results indicate that C. japonica may be a promising biological control agent for the noxious invader in China.